Insights into the Cultured Bacterial Fraction of Corals - Michael Sweet (American Society for Microbiology, 2021)
Our paper is the first study to synthesize currently available but decentralized data of cultured microbes associated with corals. We were able to collate 3,055 isolates across a number of published studies and unpublished collections from various laboratories and researchers around the world.